Anodic Materials for Electrocatalytic Ozone Generation - Yun-Hai Wang; Qing-Yun Chen (International Journal of Electrochemistry)
Ozone has wide applications in various fields. Electrocatalytic ozone generation technology as an alternative method to produce ozone is attractive. Anodic materials have significant effect on the ozone generation efficiency. The research progress on anodic materials for electrocatalytic ozone generation including the cell configuration and mechanism is addressed in this review. The lead dioxide and nickel-antimony-doped tin dioxide anode materials are introduced in detail, including their structure, property, and preparation. Advantages and disadvantages of different anode materials are also discussed.